BED EFFICIENCY FOR DISPLACEMENT WASHING OF KRAFT SOFTWOOD AND HARDWOOD PULPS - Potůček, František; Rahman, Md. Mostafizur (Editura Academiei Romane, 2018)
Using a laboratory displacement washing cell, kraft long fibre softwood and short fibre hardwood pulps cooked from spruce and a blend of deciduous woods, respectively, were subjected to displacement washing with water as a wash liquid. Based on the washing breakthrough curves measured for alkali lignin, the Peclet number was evaluated and the washing efficiency was characterised by bed efficiency at a wash liquor ratio equal to unity. For both pulps, bed efficiency increases with increasing Peclet number, however, it decreases with increasing dimensionless dispersion length. At pulp bed consistency of 120 to 130 kg m(-3), the bed efficiency of short fibre hardwood pulp was found to be greater in comparison with that of long fibre spruce pulp, which has lower permeability and greater specific hydraulic resistance. Since the displacement was the dominant mechanism during the initial period of the washing process, bed efficiency greater than unity was achieved for both pulps.
Účinnost lože při vytěsňovacím praní sulfátové jehličnanové a listnáčové buničiny
Keywords: pulp; spruce; hardwood; displacement washing; bed efficiency; dispersion; Peclet number; buničina; smrk; listnáč; vytěsňovací praní; účinnost vrstvy; disperze; Pécletovo kritérium